通过大规模平行RNA测序分析母亲血浆转录组 (2018)
提供了使用来自妊娠女性对象的样品用于诊断妊娠相关的病症、确定等位基因比、确定母亲或胎儿对于循环转录体的贡献，和/或鉴定母亲或胎儿标记物的方法。也提供了在妊娠女性对象中用于诊断妊娠相关的病症的基因的用途。 Methods are provided for diagnosing pregnancy-associated disorders, determining allelic ratios, determining maternal or fetal contributions to circulating transcripts, and/or identifying maternal or fetal markers using a sample from a pregnant female subject. Also provided is use of a gene for diagnosing a pregnancy-associated disorder in a pregnant female subject.